Pengaruh Inflasi Dan BI 7-Day Reverse Repo Rate Terhadap Profitabilitas PT. Bank BRI Syariah Tbk Periode 2017-2020 - Wiga Windy Andhini; Dedi Suselo (CV ODIS, 2022)
This study aims to determine how much influence macroeconomic factors consisting of inflation and BI 7-day reverse repo rate have on the profitability of PT. Bank BRI Syariah in 2017-2020. The population of this research is a monthly financial report of PT. Bank BRI Syariah from 2017 to 2020. The sampling in this study was determined by the purposive sampling method so that with a periode of four years, 48 samples were obtained. This study uses secondary data obtained from financial report data that has been published through the official website of PT. Bank BRI Syariah as well as inflation and BI 7-day reverse repo rate published through the official website of Bank Indonesia. The data analysis technique in this study uses the classical assumption test, multiple linear regression analysis, and the coefficient of determination test, where the data testing is assisted by the SPSS 19 application. The result in this study indicates that partially the inflation variable has no significant effect on the profitability variable, while the variable BI 7-day reverse repo rate has a significant positive effect on the profitability of PT. Bank BRI Syariah Tbk for the periode 2017-2020.